2019
DOI: 10.1002/solr.201900090
|View full text |Cite
|
Sign up to set email alerts
|

Oriented and Uniform Distribution of Dion–Jacobson Phase Perovskites Controlled by Quantum Well Barrier Thickness

Abstract: Dion–Jacobson (DJ) phase halide perovskites have attracted extensive attention in photovoltaic devices due to their significantly enhanced stability when compared with conventional 3D analogs. However, fundamental questions concerning the quantum well (QW) barrier thicknesses, which are critical to design efficient DJ phase perovskite photovoltaics, remain unknown. Herein, it is unambiguously demonstrated that QW barrier thickness, depending on bulky organic ammonium spacers with different chain lengths, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
122
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 51 publications
5
122
0
Order By: Relevance
“…), two main archetypes of layered perovskites are predominant to date, namely Ruddlesden-Popper (RP) and Dion-Jacobson (DJ) systems. [9][10][11][12][13][14][15][16][17][18][19][20] The RP structural category is defined by the S 2 A n-1 Pb n X 3n+1 formulation, which comprises an organic double layer between the inorganic layers featuring an offset per unit cell of the perovskite slab. [9][10][11][12] The DJ systems are based on the S'A n-1 Pb n X 3n+1 compositions employing organic layers (S') that stack in an almost perfect alignment between unit cells, featuring smaller interlayer space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), two main archetypes of layered perovskites are predominant to date, namely Ruddlesden-Popper (RP) and Dion-Jacobson (DJ) systems. [9][10][11][12][13][14][15][16][17][18][19][20] The RP structural category is defined by the S 2 A n-1 Pb n X 3n+1 formulation, which comprises an organic double layer between the inorganic layers featuring an offset per unit cell of the perovskite slab. [9][10][11][12] The DJ systems are based on the S'A n-1 Pb n X 3n+1 compositions employing organic layers (S') that stack in an almost perfect alignment between unit cells, featuring smaller interlayer space.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The DJ systems are based on the S'A n-1 Pb n X 3n+1 compositions employing organic layers (S') that stack in an almost perfect alignment between unit cells, featuring smaller interlayer space. [15][16][17][18][19][20] Reducing interlayer distances and tuning their mutual alignment are important parameters for controlling the optoelectronic properties as they strengthen electronic interactions between the inorganic layers and, consequently, facilitate interlayer charge transport, rendering the DJ structures superior to RP phases. [15][16][17][18][19][20] Most of the developments of layered hybrid perovskites are based on RP archetypes and there are very few examples of hybrid DJ architectures to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, Ahmad et al reported a highly efficient 13.3% DJ phase PSCs with thousand hours ultrahigh stability using the same molecule. Zheng et al reported 16.38% efficiency DJ PSCs with MAAc molten salt as solvent; Li et al reported 14.86% efficiency for (BEA) 0.5 MA 3 Pb 3 I 10 DJ PSCs. Until recently, Cohen et aland Li et al reported a novel organic spacer 1,4‐phenylenedimethanammonium (PDMA) as novel DJ perovskite, yielding 15.6% and 7% separately.…”
Section: Introductionmentioning
confidence: 99%
“…To improve upon the efficiency of these devices while preserving stability, the similar Dion–Jacobson phase perovskites (DJPs) have been of recent interest. [ 11–14 ] These materials have the typical chemical structure A'A n −1 Pb n X 3 n +1 , where n is the number of inorganic repeat layers sandwiched between the organic ligands, A' is an organic diammonium cation, A is an organic or inorganic cation, and X is a halide anion (I, Br). DJPs resemble RPPs in their structure of alternating organic and Pb‐halide layers, however they maintain several key differences.…”
Section: Introductionmentioning
confidence: 99%